Flood vulnerability analysis using geographic information system in the core zone of the Lore Lindu biosphere reserve, Indonesia - Suni, Muhammad Adam; Rahmawati, Ani; Muis, Hasriani; Maarif, Fadjri; Baharuddin, Rhamdhani Fitrah (Journal of Degraded and Mining Lands Management, 2024)
Floods are caused by the accumulation of several factors, such as global warming, climatological characteristics, hydrology, and physical conditions of an area. The purpose of this study was to map the level of flood vulnerability in the core zone of the Lore Lindu Biosphere Reserve using geographic information system (GIS) based spatial analysis with scoring and overlay. The research parameters consisted of rainfall, elevation, slope, soil type, land cover, and distance from the river. This research was conducted in the core zone divided into 13 subdistricts and 2 regencies. The results of the classification of flood vulnerability levels are divided into 4 (four) categories: not prone, low vulnerability, moderate vulnerability, and high vulnerability. The results of the analysis show that the core zone of the Lore Lindu biosphere reserve is dominated by a non-hazardous site with an area of 145,018’28 ha (67.23%), a low vulnerability zone of 65,430.10 ha (30.33%), a moderate vulnerability zone of 5,025.29 ha (2.33%), and a high vulnerability zone of 245.99 ha (0.11). Areas with a high level of vulnerability are at low elevations with flat to gentle slopes. Most land use is dominated by water, mining, and open land without vegetation and is located around rivers.